The Role of Parents in Disciplining the Implementation of the Five Daily Prayers for Teenagers at Catur Tunggal Village - Setiyawati, Ayu; Setiawan, Dedi; Arifin, M. Zainal (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The discipline in carrying out prayers is an important aspect in forming the character of teenagers who have good morals and are religious. Parents have a very big role in instilling the habit of praying five times a day in their children, especially during adolescence. This research aims to analyze the role of parents in disciplining the five daily prayers among teenagers in Catur Tunggal Village, Mesuji Makmur District. The research method used is qualitative research with a descriptive approach. Data collection techniques are carried out through observation, interviews and documentation. To ensure the validity of the data, this research uses triangulation techniques. The research results show that the role of parents in disciplining teenagers' prayers is carried out through the methods of example, habituation, supervision, as well as providing advice and punishment. With ongoing guidance from parents, teenagers become more disciplined in performing the five daily prayers and show positive changes in their attitudes and behavior. In conclusion, parents play a role as the main factor in forming prayer discipline in teenagers, which has an impact on improving the quality of their religiosity in everyday life.